Esophago-Pericardial Fistulae as a Sequela of Boerhaave Syndrome and Esophageal Stenting: A Case Report and Review of Literature. (July 2021) - Awadelkarim, Abdalaziz; Shanah, Layla; Ali, Mohammed; Alhusain, Rashid; Adam, Omeralfaroug; Subahi, Ahmed; Yassin, Ahmed S.; Lieberman, Randy
Esophago-pericardial fistulae is a rare and dreaded entity. Most reported cases in the literature were described in association with advanced upper gastrointestinal malignancies, prior surgical procedures, and radiofrequency atrial fibrillation ablation. It has been rarely reported in association with benign esophageal conditions. Surgery had been the mainstay of treatment, but there are increasingly reported cases treated successfully with esophageal stenting and pericardial drainage. In this article, we report a novel case of an esophago-pericardial fistulae occurring as a sequela of esophageal stent placed for the management of Boerhaave syndrome.